Metabolic bone disease in extremely preterm infants: incidence, risk factors, and outcomes from a structured bone health program - Alsaif, Saif; Alrahili, Mohanned; Aljarbou, Talal; Alsherbini, Lina; Maghoula, Mohammad; Alluwaymi, Alanoud; Alsenani, Mesaed; Altuwaym, Abdulrahman; Alamer, Faisal; Mandurah, Abdulrahman; Baylon, Beverly; Ali, Ibrahim; et al. (Frontiers in Pediatrics, 2025)
BackgroundMetabolic bone disease (MBD) of prematurity is a common disorder in extremely preterm and extremely low-birth-weight (ELBW) infants. However, regional data on this disorder from the Middle East are limited. We evaluated the incidence, risk factors, biochemical markers, and outcomes of MBD in infants born at <28 weeks of gestation and <1,000 g.MethodsOur retrospective cohort included 487 inborn preterm infants admitted to a tertiary NICU (Riyadh, Saudi Arabia; 2017–2024). MBD was defined as PTH >18 pmol/L at 4 weeks; ROC against radiographic osteopenia showed good discrimination (AUC 0.78). The clinical characteristics, nutrient intake, growth, and biochemical markers (ALP, phosphate, calcium, vitamin D, PTH) of the infants were analyzed. Logistic regression identified predictors and associations with adverse outcomes.ResultsMBD was diagnosed in 202 out of 487 infants (41.5%). Compared with infants without MBD, those with MBD had lower GA and birth weight (both p < 0.001), more postnatal steroid exposure (44% vs. 27%, p < 0.001), longer diuretic therapy (12% vs. 3.5%, p < 0.001), and TPN beyond 28 days (50% vs. 31%, p < 0.001). PTH and ALP values were higher, while vitamin D, calcium, and magnesium concentrations were lower (all p < 0.01). Despite similar calcium/phosphate intakes, MBD was associated with postnatal growth failure (77% vs. 64%, p = 0.005), hospitalization of >60 days (88% vs. 70%, p < 0.001), and discharge on mineral supplements (36% vs. 16%, p < 0.001). Radiologic osteopenia occurred in 17.3% of MBD infants (7.1% overall), while fractures were uncommon (1.8% overall; 4.4% in MBD). On multivariable analysis, MBD independently predicted fractures (aOR: 8.3, 95% CI: 1.01–68.3), prolonged hospitalization (aOR: 1.9, 95% CI: 1.09–3.29), and growth failure (aOR: 1.63, 95% CI: 1.06–2.53).DiscussionWithin this <28-week cohort, skeletal complications were less frequent than suggested by many reports, plausibly reflecting a structured bone health program (routine biochemical screening, optimized mineral delivery, and minimal handling). Findings support the incorporation of PTH alongside ALP for earlier detection and point to modifiable exposures (prolonged TPN, diuretics, and steroids) as targets for prevention. Prospective multicenter validation with standardized thresholds and imaging strategies is warranted.ConclusionMBD is common in extremely preterm infants and is associated with growth failure and prolonged hospitalization. A 4-week PTH screen showed good discrimination for radiologic osteopenia (AUC 0.78), supporting its role within structured bone health care. As our findings are based on a biochemical definition, diagnostic thresholds require external validation.